The Impact of Educational Interventions on Pregnant Womens Knowledge of the Childbirth Planning and Complication Prevention Program - AR, Irmayanti; Sahariah, Sahariah (Genius Journal, 2024)
Introduction: Indonesia is one of the developing countries with a high maternal mortality rate (MMR). To address this issue, the government has introduced the Childbirth Planning and Complication Prevention (P4K) program, which includes the use of P4K stickers in healthcare facilities to enhance pregnant women's awareness and enable early identification of potential pregnancy complications. Objective: This study aimed to examine the effect of education on knowledge about the P4K program among pregnant women. Method: This study employed a pre-experimental design, involving a population of all pregnant women within the service area of the Limboro Health Center, Polman Regency. A total sample of 35 pregnant women was selected using simple random sampling. Data were analyzed using the Wilcoxon test. Result: The results showed a statistically significant effect of education on knowledge about the P4K program, with a p-value of 0.00. It is concluded that education positively influences awareness and understanding of the P4K program. Conclusion: These findings highlight the importance of strengthening educational interventions to improve the implementation of the P4K program, ultimately contributing to the reduction of maternal and infant mortality in the health center's working area.